Analisis pengaruh biaya produksi, biaya distribusi dan volume penjualan terhadap laba bersih perusahaan - Lalitasari, Iven Nandia; Pratiwi, Desy Nur; Samanto, Hadi (Journal of Economics Research and Policy Studies, 2023)
This research aims to determine the effect of production costs, distribution costs, and sales volume on the company's net profit. The population of this research is food and beverage sector manufacturing companies listed on the IDX for the 2019–2022 period. This research used a purposive sampling method to obtain 76 samples. This research uses secondary data, namely financial reports of manufacturing companies in the food and beverage sector for the 2019–2022 period. The data analysis technique uses multiple linear regression tests. The research results show that production costs significantly affect net profit. The distribution cost variable has a significant effect on net profit. The sales volume variable has a significant effect on net profit. Simultaneously, the variables of production costs, distribution costs, and sales volume significantly affect net profit. The influence of research variables on net profit is 93.6 percent, and the remainder is influenced by variables other than those used in this research.